Epidemiology and Microbiology of Outpatient Cases of Carbapenem-Resistant Enterobacteriaceae in Connecticut During 2018. (October 2020) - Gupta, Simran; Leung, Vivian; Maloney, Meghan; Macierowski, Bobbie; Banach, David
Abstract : Background: Little is known about the epidemiology, microbiology, and clinical management of carbapenem-resistant Enterobacteriaceae (CRE) in outpatient settings. In Connecticut, all clinical CRE isolates are submitted to the state public health laboratory (SPHL) for a customized panel of antimicrobial susceptibility and carbapenemase gene testing. We describe all outpatient cases of CRE in Connecticut in 2018, including location of presentation, risk factors, microbiology and aspects of treatment. Methods: Outpatient CRE cases were defined as CRE infection in a patient not hospitalized at the time of positive CRE culture or within 30 days after culture collection. Outpatient cases were identified from routine statewide CRE reporting by reviewing clinical and laboratory data. A questionnaire was sent to outpatient providers who ordered the cultures that yielded CRE to collect additional clinical information. Antimicrobial susceptibility and carbapenemase gene detection results from the SPHL were also summarized. Results: Among 53 outpatient CRE cases (1 blood, 52 urine), the most common organisms were Enterobacter (25, 47%), Klebsiella (12, 23%), and E. coli (11, 21%). Overall, 21 (39.6%) patients presented in primary care settings, 8 (15%) in urology offices, 6 (11%) in women's health/OBGYN clinics; the remainder presented across various clinical settings (Fig. 1). Of 42 patients for whom clinical data were available, 45% had been hospitalized within the prior year and 19% had a chronic indwelling device. Among outpatient CRE cases, infectious diseases consultation was reported in 9.5% and lab consultation in none. Median patient age was 83 years. Of 36 CRE samples for which lab data were available, 9 (25%) were carbapenemase-producers (CP-CRE), of which 8 were bla KPC positive. Sensitivity rates to oral antimicrobials ranged from 43% to 75% (Table 1). Conclusions: CRE infections occur in several different outpatient settings, and formal ID consultation in the management of these patients is infrequent. These findings highlight the critical need for providers across different outpatient specialties to be familiar with the clinical management and infection control practices needed in caring for patients with CRE. Hospitalization within the year prior to presentation was frequent among patients who developed subsequent CRE-positive cultures. Most outpatient CP-CRE cases in CT are due to KPC production. Overall, sensitivity to oral antimicrobials frequently prescribed in outpatient settings is low, providing additional challenges to the outpatient management of patients with CRE infection. Fosfomycin, though only approved for E. coli infections, may be an acceptable antibiotic choice for the treatment of these patients. Funding: None Disclosures: None